Optical Clearing of Fixed Brain Samples Using SeeDB. Issue 1 (15th January 2014) - Ke, Meng‐Tsen; Imai, Takeshi
Abstract: Large‐scale three‐dimensional fluorescence imaging is essential for comprehensive and quantitative understanding of neuronal circuitry. We describe a water‐based optical clearing agent, SeeDB, which clears fixed brain samples in a few days leaving many types of fluorescent dyes unquenched, including fluorescent proteins and lipophilic neuronal tracers. This method maintains a constant sample volume during the clearing procedure, an important factor to keep cellular morphology intact. After optical clearing with SeeDB, we can reach a depth of >1000 µm with confocal microscopy. When combined with two‐photon microscopy, SeeDB allows us to image fixed mouse brains at millimeter‐scale level. Curr. Protoc. Neurosci . 66:2.22.1‐2.22.19. © 2014 by John Wiley & Sons, Inc.